Review of antibiotic-resistant bacteria and antibiotic resistance genes within the one health framework - Ayodele Oluwaseun Ajayi; Adebowale Toba Odeyemi; Olajide Joseph Akinjogunla; Akinwole Babafenwa Adeyeye; Ibiwumi Ayo-ajayi (Infection Ecology & Epidemiology, 2024)
Background: The interdisciplinary One Health (OH) approach recognizes that human, animal, and environmental health are all interconnected. Its ultimate goal is to promote optimal health for all through the exploration of these relationships. Antibiotic resistance (AR) is a public health challenge that has been primarily addressed within the context of human health and clinical settings. However, it has become increasingly evident that antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) that confer resistance are transmitted and circulated within humans, animals, and the environment. Therefore, to effectively address this issue, antibiotic resistance must also be considered an environmental and livestock/wildlife problem.Objective: This review was carried out to provide a broad overview of the existence of ARB and ARGs in One Health settings.Methods: Relevant studies that placed emphasis on ARB and ARGs were reviewed and key findings were accessed that illustrate the importance of One Health as a measure to tackle growing public and environmental threats.Results: In this review, we delve into the complex interplay of the three components of OH in relation to ARB and ARGs. Antibiotics used in animal husbandry and plants to promote growth, treat, and prevent infectious diseases lead to the development of antibiotic-resistant bacteria in animals. These bacteria are transmitted from animals to humans through food and environmental exposure. The environment plays a critical role in the circulation and persistence of antibiotic-resistant bacteria and genes, posing a significant threat to human and animal health. This article also highlights how ARGs are spread in the environment through the transfer of genetic material between bacteria. This transfer can occur naturally or through human activities such as the use of antibiotics in agriculture and waste management practices.Conclusion: It is important to integrate the One Health approach into the public health system to effectively tackle the emergence and spread of ARB and genes that code for resistance to different antibiotics.